PENGARUH LIMBAH CAIR INDUSTRI BATIK TERHADAP KUALITAS AIR SUNGAI LOJI DI PEKALONGAN - Safamaura, Regina Safrida; Afany, Miseri Roeslan (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2025)
Waste is one of the materials that can pollute the river. Most waste is disposed of into the river so that it will cause pollution in the river. The problem of river pollution, one of which occurs in the Loji River located in Pekalongan City, which still discharges a lot of batik waste carelessly into rivers and waterways. The research was conducted in Loji River, Pekalongan City. The purpose of this study was to determine the water quality and level of water pollution in the Loji River Pekalongan due to batik industry waste. The determination of location used survey method. The sampling method was purposive sampling based on land use activities and ease of access to water collection, which was divided into three segments, namely segment I, segment II, segment III. In each segment, two sample points were taken. Water quality was determined based on Government Regulation Number 22 of 2021 according to river water quality standards. The level of water pollution was determined by the Pollution Index (IP) method. The results showed that based on the parameters that had been tested, the water quality of the Loji River no longer met the class II water quality standards. The level of water pollution in Loji River was categorized as lightly polluted based on the pollution index. The lowest Loji River water pollution index value was 0.731 which was in the good category and the highest value was 1.725 which was in the lightly polluted category.